Degradation and toxicity of the antidepressant fluoxetine in an aqueous system by UV irradiation. (January 2022) - Pan, Chenyuan; Zhu, Feng; Wu, Minghong; Jiang, Lihui; Zhao, Xiaoyu; Yang, Ming
Abstract: Fluoxetine (FLU), a selective serotonin reuptake inhibitor, is commonly found in aquatic environments. Ultraviolet (UV) photolysis is widely used to remove certain pharmaceuticals from water and wastewater. The present study aimed to investigate the toxicity of FLU and its transformed products formed during UV photolysis by using zebrafish embryos ( Danio rerio ) as a model. The degradation rates of FLU for five days were approximately 63.6% ± 2.14%, 84.6% ± 0.99%, and 97.5% ± 0.25% after 15, 30, and 60 min of UV irradiation, respectively. Furthermore, the degradation mechanism was explored using LC-MS measurements and density flooding theory (DFT) theoretical calculations. Comprehensive toxicity preassessment of FLU and its degradation products was carried out using the T.E.S.T. software. The effects of physiological and biochemical parameters and neuron- and apoptosis-related gene expression were examined in zebrafish embryos exposed to non-irradiated (0-min) and irradiated (15, 30- and 60-min) solutions from 4 h post-fertilization (hpf) to 120 hpf. The hatching time of zebrafish embryos exposed to the non-irradiated solution (0-min) and irradiated solution (60-min) was delayed, their heart rate at 48 and 72 hpf increased, and their body length at 120 hpf decreased. Significant differences were found between the non-irradiated (0-min) and UV-irradiated (15- or 30-min) groups. A dynamic response involving acetylcholinesterase (AChE) and superoxide dismutase (SOD) activity was also observed in the non-irradiated and UV-irradiated groups. During the UV treatment experiments, the expression levels of neuron-related and apoptosis-related genes were significantly reduced over time alongside the formation of FLU degradation products. Overall, this study provides new concepts to remove and assess the toxicity of emerging contaminants in aquatic environments and highlights the need to consider the formation and persistence of toxic transformation products. Graphical abstract: Image 1 Highlights: The degradation of Fluoxetine (FLU) was effective in aqueous solution by UV irradiation. The toxicity effects on zebrafish embryos were occurred in aqueous system during the UV irradiation. The mixture toxicity of degradation products is an important consideration when assessing environmental risk.